Enhancing mechanical and freeze-thaw performance of MICP-treated sand through palm fiber reinforcement: A sustainable approach for sandy soil stabilization - Huan Tao; Chaochao Sun; Jili Qu; Yuandong Huang (PLoS ONE, 2025)
The integration of palm fiber with Microbially Induced Calcite Precipitation (MICP) technology offers a sustainable and bio-based approach to enhance the mechanical performance and durability of sandy soils, particularly under freeze-thaw conditions. In this study, a systematic experimental investigation examines the effects of varying palm fiber contents (0%−0.30%) on the bearing capacity, crust thickness, calcium carbonate deposition, and freeze-thaw resistance of MICP-treated sand. Results indicate that mechanical performance improves with increasing fiber content, peaking at 0.15%, beyond which the benefits diminish due to fiber agglomeration. At the optimal dosage, the bearing capacity increases by 24%, crust thickness by 70.5%, and calcium carbonate content reaches 16.8% compared to fiber-free MICP samples. Freeze-thaw tests demonstrate higher mass and strength retention, indicating improved durability. Microstructural analyses using SEM, XRD, EDS, and FTIR reveal enhanced microbial attachment and uniform CaCO₃ precipitation along fiber-sand interfaces, which strengthens matrix cohesion. These findings uncover a hybrid bio-mechanical reinforcement mechanism and highlight the trade-offs between fiber dosage and pore connectivity. This study provides novel insights into fiber-assisted biomineralization and offers a viable pathway for environmentally friendly soil reinforcement. Furthermore, potential directions such as predictive modeling, biodegradability assessments, and field-scale application are proposed to support long-term geotechnical and ecological engineering deployment.